POLYPHONY OF UKRAINIAN BAROQUE PARTES IN THE LIGHT OF THE MEDIEVAL THEORY OF MODALITY - Shumilina, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The traditions of Ukrainian partes singing, which developed in the East Slavic territories during the 17th and first half of the 18th centuries, have been studied widely and in various ways, however, some issues still remain unresolved. One of them is the influence of the medieval theory of modality on the pitch organization of polyphony in partes singing. Main objective(s) of the study. The purpose of the article is to review the main provisions of the medieval theory of modality in its projection on the polyphony of Ukrainian partes singing. The scientific novelty consists in identifying manifestations of medieval modal theory in the polyphony of Ukrainian partes, which affected the specificity and main features of partes art. Methodology. The methodological basis is made up of general scientific methods: study and generalization, abstraction and formalization, systematic analysis and synthesis. Results / findings and conclusions The main provisions of the medieval theory of modality, which became the basis of polyphony in church music of the Middle Ages, the Renaissance, and partly the Baroque, are studied. The main features of this system, which were described in the works of famous European theorists (Guido d’Arezzo, H. Glarean, G. Zarlino, etc.), are indicated. The influence of the main provisions of the medieval theory of modality on Ukrainian partes polyphony, which represents the Baroque era, is revealed. In the process of analyzing the main provisions of the medieval theory of modality in their projection onto the features of Ukrainian baroque partes, the main attention was paid to the system of hexachords, on the basis of which polyphony was formed with the dominance of interval and triadic consonances, modal tonality, formed on the basis of natural-mode mesatonic in its projection onto the polyphonic vertical, specific types of cadences that arose under the influence of the time organization of musical compositions of vocal polyphony of a strict style and had modal chromaticisms and dissonant consonances, the issue of the weakness of the tonal center and functional connections between triads, etc. The material for the study was the discovered four-part concertos by Mykola Dyletsky.